RESURGENCY OF SUFI ISLAM IN INDONESIA: FROM THE PERIPHERY TO THE CENTER - Budi Rahman Hakim (ILMU USHULUDDIN, 2025)
This article is about the re-emergence of Sufi Islam in Indonesia, which is a huge turnaround from the periphery towards the core of spiritual and social life. Based on a literature review, the article discovers that Sufism has been revitalized in the following four areas: (1) doctrinal renovation through the Neo-Sufism paradigm, (2) reformatting of tarekat's social spaces in education, economic empowerment, and healthcare services, (3) infiltration of Sufi values into cyber culture through social media and online da'wah, and (4) Sufism as a type of social and cultural capital that determines public morals and social cohesion. Based on the above discoveries, the article confirms that Sufism has survived and has become a spiritual and social force that is responsive to the current challenges as well as strengthening the strengthen the weak version of Islam and the values of Islam Nusantara in the urban society in Indonesia.